Development of Policy Instruments in an Effort to Increase Tax-to-Gross Domestic Bruto Ratio in Indonesia - Pramubinawan, Dyansaputra (Journal of Governance and Social Policy, 2023)
The tax revenue ratio is seen as a better indicator for determining the contribution of tax revenue in the economy of a country in low performance with Gross Domestic Product. The World Bank stated that a tax to GDP ratio of at least 15% would produce positive economic growth and could be a long- term solution to overcoming poverty. However, efforts to increase the tax to GDP ratio are not an easy challenge for developing countries, including Indonesia. Efforts to find solutions to these challenges have also been a never-ending task for the Indonesian tax authorities for almost the last ten years. Using qualitative methods, this article tries to identify policy instruments that have been implemented and developed by the Directorate General of Taxes as the main agency collecting state revenues in Indonesia.